Indigenous Theatre as Resistance: Toronto as a Nexus for Canada’s Burgeoning Indigenous Theatre Scene from Late 1980s to Early 1990s - Raphaela Pavlakos (Theatre Academy)
The late 1980s and early 1990s were times of great development for the Indigenous Theatre scene in Toronto, Canada’s largest city. This paper seeks to provide a closer look at the development of an Indigenous Theatre scene, a space on the fringes of traditional and hegemonic Canadian cultural production. This space, created by and for Indigenous creatives, made space for Indigenous voices and storytelling that did not yet exist to such a degree across Canada. The creation of this space led to the expansion of Indigenous Theatre across Canada and North America, as well as established mainstream interest and space for Indigenous voices, something that was felt through Indigenous activism of this time. By taking a closer look at Canada’s first Indigenous Theatre company, Native Earth Performing Arts, which is based in Toronto, as well as analyzing two fundamental texts, Drew Hayden Taylor’s (Curve Lake First Nations) Toronto at Dreamer’s Rock and Daniel David Moses’ (Delaware/Tuscarora) Almighty Voice and His Wife, this paper will trace the common themes in these two texts that were prevalent in the work of this time, as well as unpack the connection these plays have to place, specifically in their relation to Toronto and the Indigenous Theatre scene there.